Dysregulation of hepatic metabolism with obesity: factors influencing glucose and lipid metabolism. Issue 1 (2nd March 2022) - Nagarajan, S. R.; Cross, E.; Sanna, F.; Hodson, L.
Abstract : The liver is a key metabolic organ that undertakes a multitude of physiological processes over the course of a day, including intrahepatic lipid and glucose metabolism which plays a key role in the regulation of systemic lipid and glucose concentrations. It serves as an intermediary organ between exogenous (dietary) and endogenous energy supply to extrahepatic organs. Thus, perturbations in hepatic metabolism can impact widely on metabolic disease risk. For example, the accumulation of intra-hepatocellular TAG (IHTG), for which adiposity is almost invariably a causative factor may result in dysregulation of metabolic pathways. Accumulation of IHTG is likely due to an imbalance between fatty acid delivery, synthesis and removal (via oxidation or export as TAG) from the liver; insulin plays a key role in all of these processes.